Knowledge of drum set tuning in jazz / Faeez Ikhwan Abdul Halim - Abdul Halim, Faeez Ikhwan (2013)
The study was carried out to educate beginner and student drummers regarding the knowledge of drum set tuning in jazz genre. The objective of this research is to explain and provide guidelines for beginner and student drummer the proper way of tuning their drum set in order to get the sound that they desire. This study will also find solution that drummers face regarding the different type of tuning method exposed to them. Lastly, this research will then find the best tuning method in order for drummers to get the best out of their drum set.